Expertise in Evaluating Choreographic Creativity: An Online Variation of the Consensual Assessment Technique - Clements, Lucie; Redding, Emma; Sell, Naomi Lefebvre; May, Jon (Frontiers in Psychology, 2018)
In contemporary dance, experts evaluate creativity in competitions, auditions, and performances, typically through ratings of choreography or improvisation. Audiences also implicitly evaluate choreographic creativity, so dancers' livelihoods also hinge upon the opinions of non-expert observers. However, some argue that the abstract and often pedestrian nature of contemporary dance confuses non-expert audiences. Therefore, agreement regarding creativity and appreciation amongst experts and non-experts may be low. Finding appropriate methodologies for reliable and real-world creativity evaluation remains the subject of considerable debate within the psychology creativity research field. Although considerably variant in methodological operationalisation, the Consensual Assessment Technique (CAT) asks individuals to use an implicit definition to assess creativity in others' work. This study aimed to investigate the role of experience and expertise in the evaluation of choreographic creativity, with a secondary aim of testing the feasibility of an online snowballing methodology for large-scale dance-specific research, informed by the methodology of the CAT. We filmed 23 Contemporary Dance students each performing a 3-minute peer-choreographed solo and then recruited 850 online evaluators with varying degrees of expertise and experience in dance and creativity. Evaluators viewed at least one randomly selected video and rated creativity, technical ability, appreciation and understanding of the work, each using a seven-point Likert scale. A one-way ANOVA showed a significant difference in creativity ratings across the 23 videos, and creativity correlated significantly with the other variables. We then categorised evaluators on nine aspects of their dance and creative experience and entered the data into a repeated-measures linear mixed model. Two of the fixed effects yielded differences in creativity evaluations: (i) contemporary choreographic experience and (ii) self-reported creative expertise, as did the random effect of the video. The results indicate that personal experience of the choreographic process impacts creativity assessment, above and beyond experience in dance class participation. Implications for creativity assessment within creativity research and practice are discussed.